Sexuality and society in the medical context: Conceptualization, implementation and evaluation of a student-led elective course in medical school at Leipzig University - Endres, Konrad Jakob; Surber, Chiara; Albertus, Mona; Müller, Martina; Wortmann, Laura; Heinz, Nick; Conrad, Ines; Götze, Heide (GMS Journal for Medical Education, 2025)
Objectives: Physicians often avoid discussing sexual and gender-related health with patients due to discomfort and fear of causing offense, leading to incomplete sexual histories and gaps in care, particularly affecting LGBTQI+ patients who face significant health disparities. This project aimed to address this gap by introducing an elective course titled “Sexuality and Society in the Medical Context” to provide German medical students with the skills and knowledge necessary for effective sexual health discussions. Methods: The course utilized interactive teaching methods, including peer learning and role-playing. Topics covered ranged from sexually transmitted infections to gender diversity and LGBTQI+ health. Student feedback was collected through a structured evaluation to assess the course’s impact and effectiveness. Results: Student feedback was highly positive; with participants highlighting the course’s engaging format and relevance to their medical education. The evaluation showed high satisfaction with the course's organization, content, and interactive elements. Conclusion: Although the elective course was well received, its limited scope suggests the need to integrate similar training into the core medical curriculum. This integration is crucial for enabling future physicians to systematically address sexual health issues, overcome systematic biases, and foster a supportive environment for all patients.